2007
DOI: 10.1159/000106356
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Fetoscopic Tracheal Balloon Occlusion Enhanced by Hyperoncotic Lung Distension: Is There a Role in the Treatment of Fetal Pulmonary Hypoplasia from Early Preterm Premature Rupture of Membranes?

Abstract: Objectives: To assess the effect of fetoscopic tracheal occlusion (FETO) enhanced by hyperoncotic distension on pulmonary hypoplasia from preterm premature rupture of membranes prior to 22 weeks of gestation (ePPROM). Methods and Results: In a fetus with ePPROM since 19+5 weeks of gestation, MRI at 28+2 weeks provided a lung volume of 10 ml. FETO enhanced by hyperoncotic distension was performed at 28+3 weeks. After 4–5 days, balloon dislodgement was observed. The lung volume increased to 18 ml. The baby was b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 21 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…6 and 28 ? 3 weeks of gestation in three fetuses with severe fetal pulmonary compression/ hypoplasia from ePPROM [78,79]. In each case, tracheal occlusion resulted in stunningly fast improvements in lung volume and survival.…”
Section: Fetoscopic Tracheal Balloon Occlusion In Fetuses With Diaphrmentioning
confidence: 96%
“…6 and 28 ? 3 weeks of gestation in three fetuses with severe fetal pulmonary compression/ hypoplasia from ePPROM [78,79]. In each case, tracheal occlusion resulted in stunningly fast improvements in lung volume and survival.…”
Section: Fetoscopic Tracheal Balloon Occlusion In Fetuses With Diaphrmentioning
confidence: 96%
“…[31][32][33] More recent studies have also suggested that fetuses with very early and prolonged premature rupture of the membranes may also benefit from fetal tracheal occlusion. [34][35][36] Fetal lung volumetric analysis may also be useful for the selection process in those cases.…”
Section: Fetal Lung Volumementioning
confidence: 99%
“…Fetal tracheoscopy for balloon removal is also possible when the patient ruptures membranes subsequently and develops oligohydramnios. As a consequence, one could also consider applying FETO in case of persistent oligohydramnios as a consequence of spontaneous preterm prelabour rupture of membranes (PPROM), as described by Kohl et al 51 The main limitation, however, to this investigational indication is the absence of validated criteria for lethal lung hypoplasia because of PPROM.…”
Section: Congenital Diaphragmatic Herniamentioning
confidence: 99%